2013
DOI: 10.2174/15733998113099990061
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Overweight, Obesity, and Type 2 Diabetes Among Asian American Subgroups

Abstract: This systematic review synthesizes data published between 1988 and 2009 on mean BMI and prevalence of overweight, obesity, and type 2 diabetes among Asian subgroups in the U.S. We conducted systematic searches in PubMed for peer-reviewed, English-language citations that reported mean BMI and percent overweight, obesity, and diabetes among South Asians/Asian Indians, Chinese, Filipinos, Koreans, and Vietnamese. We identified 647 database citations and 23 additional citations from hand-searching. After screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 95 publications
(169 reference statements)
4
59
2
Order By: Relevance
“…Our study also confirmed that males were more likely to be overweight or obese than females. Our percentages were not as high as California's government data, which indicated high propensity for obesity among Asians [30]. However, their data included a variety of Asian groups.…”
Section: Discussioncontrasting
confidence: 77%
“…Our study also confirmed that males were more likely to be overweight or obese than females. Our percentages were not as high as California's government data, which indicated high propensity for obesity among Asians [30]. However, their data included a variety of Asian groups.…”
Section: Discussioncontrasting
confidence: 77%
“…A key issue is that Filipino Americans have a higher mean BMI in comparison to other Asian American subgroups. 12 Second, more than one third of Filipino Americans (38%) are physically inactive, which is a higher rate than that noted for Chinese Americans. 13,14 Obesity and physical inactivity do not, however, completely explain the higher prevalence of diabetes among Filipino Americans in comparison to non-Hispanic whites in the US.…”
mentioning
confidence: 86%
“…Individuals of South Asian (Bangladeshi, Indian, Nepali, Pakistani, and Sri Lankan) origins are at particular risk of severe early onset CVD and type 2 diabetes, even before the development of obesity (9)(10)(11). Metabolic risk factors such as waist circumference, dyslipidemia, and deregulation of glucose and insulin often underlie oxidative stress and atherosclerotic changes in this population (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%